Cooper concentration and tiáue distribution in rainbow trout (oncorhynchus mykiá) reared in Spanish fish farms - Carbonell, G.=700 1 Tarazona, J.V.
(En, Es)
Ilus., 37 ref.
Keywords: ONCORHYNCHUS MYKIá; ANALISIS DE TEJIDOS; CONCENTRACION; COBRE; TEJIDOS ANIMALES; TOXICIDAD; ESPAÑA; TRUCHA ARCO IRIS; INVESTIGACION AGRARIA